Social interactivity and member roles in Digimon fandom group: a netnography study - Rizki Briandana; Harris Christanto (Faculty of Communications Science, Dr. Soetomo University, 2023)
Digi-In stands as Indonesia's largest Digimon fan community, boasting the highest level of member participation and interaction through its Facebook group platform. This study investigates the dynamics of social interaction and the roles played by members within the Digi-In Facebook group, specifically in the Digimon Adventure 2020 animation context. The research framework draws upon the Sense of Community Theory and Groundswell Concept. Employing a constructivist paradigm, a descriptive qualitative approach, and the netnography method, this study relies on participant observation and interviews for data collection and Cyber Media Analysis for data analysis. The findings reveal that the Digi-In community fosters social interactivity among Digimon enthusiasts, facilitating the exchange of up-to-date information, promoting the trading of Digimon collectables, and enhancing members' photography and videography skills. The open communication within the Digi-In community provides opportunities for industry collaboration to boost customer engagement and allows animators to align their creative work with market demands.